Policy Brief—Achieving Paris Climate Agreement Pledges: Alternative Designs for Linking Emissions Trading Systems. (10th February 2018) - Rose, Adam; Wei, Dan; Miller, Noah; Vandyck, Toon; Flachsland, Christian
Abstract: The coordination of international climate policy, such as linking systems of tradable greenhouse gas (GHG) emissions allowances, can greatly lower the cost to all participants of slowing climate change. We consider alternative policy designs of international agreements that would help implement the 2015 Paris Climate Agreement's GHG reduction pledges. In particular, we examine a stepwise approach to implementing a global system of GHG emissions trading, which includes estimating the benefits of alternative configurations of participating countries. We also illustrate the importance of allowance trading design features, such as the transfer of auction revenues to low-income countries. Numerical simulations indicate that an emissions trading system covering the power and industry sectors in all countries that made unconditional pledges could reduce the associated mitigation costs by more than 72 percent. Moreover, transferring the revenues from the sale of emission allowances could greatly enhance the capability of lower-income countries to meet their Paris Agreement pledges.